EFEKTIVITAS PUPUK SILIKAT (Orrin) TERHADAP PERTUMBUHAN VEGETATIF DAN KESIAPAN ADOPSI TEKNOLOGI PADA PETANI BAWANG MERAH DI LOMBOK UTARA - Rika Andriati Sukma Dewi; Isnaniar Rahmatul Azizah; Fadli Fadli; Nurhalisah Nurhalisah; Muhammad Jipri Yadi Saputra (Jurnal Abdi Insani, 2025)
Shallots are a strategic horticultural commodity with high economic value, making them a crucial source of income for farmers in North Lombok. However, their productivity remains relatively low, largely due to the intensive use of chemical fertilizers, which contributes to the degradation of soil fertility. Therefore, this community engagement activity aimed to introduce and assist farmers in Anyar Village—particularly members of the Lembah Subur Farmer Group—in applying silicate-based fertilizer technology to shallot cultivation. The methodology included problem identification, socialization of liquid silicate fertilizer, implementation of comparative demonstration plots between the use of silicate-based fertilizer (Orrin) and conventional farming practices commonly adopted by farmers, as well as technical field assistance. The results revealed a positive response from farmers toward the implementation of Orrin fertilizer, both in terms of application simplicity and fertilization cost efficiency. Visually, shallot plants treated with Orrin exhibited more optimal vegetative growth, characterized by more erect posture, greener leaves, and a higher number of leaves compared to plants without Orrin application. This positive response indicates farmers’ readiness to adopt environmentally friendly technologies with the potential to enhance productivity. The application of silicate fertilizer (Orrin) proved effective in improving the vegetative growth of shallots and increasing farmers’ awareness of the significance of sustainable fertilization innovations.